FIVE FORCES ANALYSIS OF COFFEE BUSINESS INDUSTRY IN TEMANGGUNG REGENCY OF CENTRAL JAVA - Muhammad Setiawan Kusmulyono; Rathria Arrina Rachman; Vania Pradipta Gunawan (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
Coffee is a valuable commodity whose popularity is increasing and substantially contributes to economic growth. Coffee is an essential asset on a global scale, and the market has been continuously rising over the past 30 years. Temanggung, in Central Java, is one of the most well-known coffee-producing regions with a unique character. Temanggung is remarkable because it has two geographical indication certificates, Sindoro Sumbing Arabica, and Temanggung Robusta, and is the largest Arabica and Robusta coffee-producing area in Central Java. This study aimed to investigate the competitive landscape using Porter's Five Forces by applying qualitative research to the coffee business in Temanggung. The study's findings revealed that by understanding the capabilities of each force in the industry for each category of business actor and coffee bean type, stakeholders could gain unique knowledge about the coffee industry, particularly the problems throughout the value chain. This research is useful in assisting business actors and other stakeholders in making the best possible decisions. Finally, this research can assist central and local governments in efficiently promoting Indonesia's increasingly promising coffee sector in the future.